2022
DOI: 10.1038/s41398-022-02014-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct promoter regions of the oxytocin receptor gene are hypomethylated in Prader-Willi syndrome and in Prader-Willi syndrome associated psychosis

Abstract: Prader-Willi syndrome (PWS) is a rare neurodevelopmental disorder caused by a loss of usually paternally expressed, maternally imprinted genes located on chromosome 15q11-q13. Individuals with PWS display a specific behavioral phenotype and have a higher susceptibility than the general population for certain psychiatric conditions, especially psychosis. An impairment of the oxytocin system has been described in Prader-Willi syndrome, but has not yet been investigated in detail on the epigenetic level. Recent s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…However, given that OXT receptors in Magel2 KO mice are downregulated (24), it is likely that the increased activity results from homeostatic compensation. A similar compensation is seen in PWS patients – while on one hand they report reduced methylation of OXT-receptor (25) and increased plasma OXT (26), treatment with OXT-receptor agonist improves symptoms of PWS in some clinical studies (2729) (but not others (30)). Furthermore, spike broadening of OXT neurons as seen here is observed during lactation (31,32), suggesting that reduction of Ca 2+ spike duration observed in Magel2 KO mice reflects a physiologically relevant deficit.…”
Section: Discussionmentioning
confidence: 70%
“…However, given that OXT receptors in Magel2 KO mice are downregulated (24), it is likely that the increased activity results from homeostatic compensation. A similar compensation is seen in PWS patients – while on one hand they report reduced methylation of OXT-receptor (25) and increased plasma OXT (26), treatment with OXT-receptor agonist improves symptoms of PWS in some clinical studies (2729) (but not others (30)). Furthermore, spike broadening of OXT neurons as seen here is observed during lactation (31,32), suggesting that reduction of Ca 2+ spike duration observed in Magel2 KO mice reflects a physiologically relevant deficit.…”
Section: Discussionmentioning
confidence: 70%
“…A recent study reported lower methylation of the OXTR exon region 1 in males with PWS with psychosis compared to those without psychosis ( 28 ). We found no difference in OT or AVP levels between people with PWS with and without psychosis, however, only five individuals with PWS in our cohort had psychosis.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported lower methylation in the intron 1 region of the OT receptor gene in DNA blood samples of individuals with PWS compared to age-, sex-and body mass index (BMI) matched controls. The authors further found males with PWS and psychosis showed significantly lower methylation of the OXTR exon region 1 than those without psychosis, suggesting that an OT deficiency in PWS might be associated with the higher rate of psychosis found in PWS (28). Regarding brain function, PWS has long been considered a disorder of the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prader–Willi Syndrome (PWS) is a rare neurodevelopmental disorder caused by a loss of paternally expressed genes on chromosome 15q11-q13 [ 1 ]. PWS newborn individuals are characterized by hypotonia that can lead to difficulties in sucking and require assisted feeding.…”
Section: Introductionmentioning
confidence: 99%